Antioxidant properties of Ageratum conyzoides L. Asteraceae leaves - Adetuyi, FO; Karigidi, KO; Akintimehin, ES; Adeyemo, ON (Bangladesh Journal of Scientific and Industrial Research, 2018)
In vitro antioxidative and anti-lipid peroxidative properties of aqueous and methanol extracts of Ageratum conyzoides leaves were studied in controlling erectile dysfunction caused by oxidative stress. Methanol extract gave a significantly (P ˂ 0.05) higher content of total phenolic (61.4 mgGAE/g), total flavonoid (42.2 mgQE/g), ascorbic (10.1 mgAAE/100g) and phosphomolybdate (45.8 mgAAE/g) than the aqueous extract. The result showed that the extracts have high antioxidant activities. However, the methanol extract showed a higher DPPH and hydrogen peroxide scavenging activities over aqueous extract but the aqueous extract had a higher reducing power. The methanol extract exhibited a greater inhibition against lipid peroxidation induced by Fe2+ in rat pancreas and penile tissue homogenate exemplified by their least IC50 (94.21 μg/ml in pancreas) and (75.95 μg/mL in penile tissue) while in rat brain homogenate the aqueous extract exhibited a greater inhibition against lipid peroxidation induced by Fe2+ with least IC50 of 91.74 μg/mL. Hence, these extracts can be used as a potent natural antioxidant against free radicals and as a natural source of combating erectile dysfunction caused by oxidative stress. The extracts of Ageratum conyzoides leaves could be useful therapeutically as erectogenic agent. Bangladesh J. Sci. Ind. Res.53(4), 265-276, 2018